A Two‐Phase Approach to Fusicoccane Synthesis To Uncover a Compound That Reduces Tumourigenesis in Pancreatic Cancer Cells. Issue 19 (25th February 2022) - Chen, Bolin; Wu, Qianwei; Xu, Dongdong; Zhang, Xijing; Ding, Yahui; Bao, Shiqi; Zhang, Xuemei; Wang, Liang; Chen, Yue
Abstract: Alterbrassicicene D (1 ) and 3(11)‐epoxyhypoestenone (2 ) were synthesised via a two‐phase approach featuring concise construction of the 5‐8‐5 tricyclic intermediate and a tandem base‐mediated epoxide opening–transannular oxa‐Michael addition cascade to forge the complex skeleton of 2 . The route is scalable and we generated 15 g of the tricyclic intermediate in 8 steps from ( R )‐limonene and 720 mg of the penultimate bioactive intermediate in a protecting‐group‐free manner. Our synthesis enabled the structural determination of 2 and provided materials for preliminary anticancer evaluation. The penultimate intermediate showed therapeutic potential in terms of its ability to dramatically reduce the tumourigenic potential of PANC‐1 pancreatic cancer cells according to a limiting dilution tumour‐initiating assay. Our synthetic approach will facilitate unified access to naturally occurring fusicoccanes and their derivatives for anticancer evaluation. Abstract : A two‐phase route for the synthesis of fusicoccane diterpenes enabled the total synthesis of alterbrassicicene D (1 ) and 3(11)‐epoxyhypoestenone (2 ) and the structural determination of 2 . The route yielded 15 g of 3 in eight steps from ( R )‐limonene and 720 mg of the penultimate intermediate in a protecting‐group‐free manner. This penultimate intermediate was found to have tumourigenesis‐abolishing potential.